2022
DOI: 10.1109/ojim.2022.3190535
|View full text |Cite
|
Sign up to set email alerts
|

Effective Convolutional Transformer for Highly Accurate Planetary Gearbox Fault Diagnosis

Abstract: To extract the global temporal correlations and local features together to enhance the accuracy for fault diagnosis, this paper proposes an effective convolutional Transformer (ECT), which can learn the global temporal correlations using Transformer and local features with convolution at the same time. The proposed method designs a multi-stage hierarchical structure of Transformer, which utilizes convolutional tokenization to distill dominating sequence features from raw vibration signals while increasing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The dimension of this transformed output equals the dimension of the original input vector. Typically, the first layer of the block has 4 times more neurons than the last layer of the block [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The dimension of this transformed output equals the dimension of the original input vector. Typically, the first layer of the block has 4 times more neurons than the last layer of the block [ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…The performance of the ER is crucial since it directly influences the overall functionality of the controlled system, particularly for hypersonic aircraft, and impacts control accuracy and hit rates [ 6 ]. For most mechanical devices, such as motor bearings, self-priming centrifugal pumps, and axial piston hydraulic pumps [ 22 , 23 , 24 , 25 , 26 ], FD typically entails the analysis of sensor data collected during actual operations. However, given the stringent safety, controllability, and repeatability requirements, along with the limitations in the quantity and quality of field tests for hypersonic aircraft, extensive research has been conducted on ground-based semi-physical simulation technology.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…To exploit the merits of both CNN and transformer, Han et al [124] proposed a Convformer-NSE to extract the local and global information from raw vibration signals, in which two convolutional layers were added to process input data and a novel Senet (NSE) [125]was integrated with transformer to make full use of learning of channel and spatial adaptivity. Sun et al [126] designed a multi-stage hierarchical structure via convolutional tokenization for transformer to learn both local and global information from raw signals, and meantime, spatial-reduction attention and linear dimension reduction projections were introduced to transformer to reduce the resource consumption. Li et al [118] proposed a variational attentionbased transformer network (VATN) as shown in figure 15, in which the basic transformer model was improved by a sparse constrain to embed prior knowledge into the model.…”
Section: Transformermentioning
confidence: 99%